Assessment of Regulatory Policy for Public Relations Practice in Nigeria - Ikemefuna, Maha Jude; Igyuve, Anthony I.; Ogande, Anthony (Darul Yasin Al Sys, 2025)
This study examines the regulatory policy governing Public Relations (PR) practice in Nigeria, with a focus on its effectiveness in promoting ethical standards and professionalism. Adopting a survey research design, the study is anchored on the Excellence Theory and the Synergistic Communication for Development (SCD) model, which together emphasize strategic communication and collaborative development approaches. A sample of 333 respondents was determined using the Taro Yamane sample size formula, and data were collected using structured questionnaires. Findings reveal that a majority of respondents believe the application of regulatory policies in PR practice encourages adherence to global standards and discourages ethical violations. Furthermore, the implementation of these policies has contributed to a reduction in unprofessional practices, thereby enhancing the overall effectiveness of regulatory frameworks in the Nigerian PR industry. The study concludes that regulatory policies are largely effective in promoting professionalism in PR practice. It recommends, among other measures, that regulatory bodies streamline administrative registration processes to encourage wider enrollment and compliance, ultimately fostering a more ethical and standardized PR profession in Nigeria.